Development and Formative Evaluation of a Low-Fidelity Equine Castration Model for Veterinary Education - Sheats, M. Katie; Burke, Megan J.; Robertson, James B.; Fiebrandt, Katherine E.; Fogle, Callie A. (Frontiers in Veterinary Science, 2021)
Entrustable Professional Activities (EPAs) are units of activity that early-stage professionals perform in the workplace that necessitates simultaneous integration of multiple competencies. EPA #6 requires students to perform a common surgical procedure on a stable patient, including pre-operative and post-operative management. Castration is one of the most common surgeries performed by equine primary care practitioners and is considered an “entry-level competency” for veterinary graduates entering equine private practice, however, to our knowledge there are no equine castration models available for veterinary student education. Therefore, we developed an inexpensive, low-fidelity model of equine field castration and evaluated it using a mixed-methods approach. Two different groups of students, with or without model experience, completed surveys before and after live horse castration. Students who used the model also completed model specific surveys. Videos of the students completing the model were evaluated by at least two different equine veterinary faculty using a 15-point rubric, and inter-rater reliability of the rubric was determined. After completing the model, students reflected on strengths and weaknesses of their performance. From our student survey results, we determined that student attitudes towards the model were mostly positive. Interestingly, there were several student attitudes towards the model that became significantly more favorable after live horse castration. Prior to live horse castration, there was no significant difference in confidence in model vs. no-model groups. Following live horse castration, students who used the model had higher confidence in procedure preparation and hand-ties than students who did not use the model, but they had lower scores for confidence during patient recovery. When reflecting on model castration, students most commonly cited preparation and surgical description as strengths, and ligature placement and hand-ties as weaknesses. Experts provided several suggestions to improve the model, including incorporation of emasculators and the need for better model stabilization. Our findings suggest that both students and veterinary educators feel that this low-fidelity model has educational value. Rubric performance metrics were favorable, but additional steps are needed to improve grading consistency among educators. Future research will determine whether student performance on the model is predictive of competence score during live-horse castration.